A study of the relationship between social network on academic performance and non academic engagement towards student in UiTM Samarahan / Zaimastura Junaidi - Junaidi, Zaimastura (Faculty of Business and Management, Universiti Teknologi MARA Sarawak, 2015)
The purpose of this study is to identify the relationship between social network and (academic performance, non academic engagement), and the relationship between academic performance and non academic engagement towards student in UiTM Samarahan, Sarawak. Also this research aims to contribute a better understanding of these relationships. The data set is collected through self-administered questionnaire and convenient non probability random sampling method. A sample of 331 was collected from UiTM Samarahan, Sarawak. The findings revealed that there is a positive significant relationship between social network and (academic performance, non academic engagement) and the relationship between academic performance and non academic engagement. The objectives were tested through correlation analysis. The findings of this study are limited by the number of respondents, area and location.